Seasonal migration of labor in the autumn lean period: Evidence from Kurigram district, Bangladesh - Shahriar, Abu Zafar Md; Zeba, Sakiba; A S M Parves, Shonchoy; Parveen, Shaila (BRAC University, 2010)
Cataloged from PDF version of report.